2006
DOI: 10.1038/sj.npp.1301074
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 Activation in Rat Frontal Cortex Following Treatment with Typical and Atypical Antipsychotics

Abstract: In schizophrenia, studies indicate that apoptotic susceptibility in cortex may be increased. A role for apoptosis in schizophrenia could potentially contribute to post-mortem evidence of reduced cortical neuropil and neuroimaging studies showing progressive cortical gray matter loss. Interestingly, antipsychotic treatment has been associated with higher cortical levels of anti-apoptotic Bcl-2 protein in rat cortex and preliminary data has suggested a similar association in schizophrenia and bipolar disorder. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…A number of mechanisms have been suggested for HAL-induced cytotoxicity, including necrotic and apoptotic mechanisms. The increased caspase-3 activity in cultured neurons continuously exposed to HAL for 24 h is consistent with the earlier reports in rats (Ukai et al, 2004;Jarskog et al, 2007). Some studies have reported a caspase-independent pathway-mediated cell death by HAL (Wei et al, 2006;Crawford and Bowen, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A number of mechanisms have been suggested for HAL-induced cytotoxicity, including necrotic and apoptotic mechanisms. The increased caspase-3 activity in cultured neurons continuously exposed to HAL for 24 h is consistent with the earlier reports in rats (Ukai et al, 2004;Jarskog et al, 2007). Some studies have reported a caspase-independent pathway-mediated cell death by HAL (Wei et al, 2006;Crawford and Bowen, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…The support for this hypothesis is based upon reports of significant alterations of the proteins Bcl-2 and Bax (specifically the Bax/Bcl-2 ratio) in brain regions that are known to be important to the symptomatology of the schizophrenia, such as temporal cortex (Jarskog et al, 2004). Interestingly, short-term rodent studies have indicated an upregulation of antiapoptotic markers following treatment with olanzapine and clozapine (He et al, 2004;Bai et al, 2004), but showed increased activation of caspase-3, an apoptotic marker, with chronic use of both typical and atypical antipsychotics (Jarskog et al, 2007). Other studies in rodents have indicated that typical and atypical antipsychotics can have favorable or unfavorable effects on brain levels of BDNF (and other neurotrophins such as nerve growth factor) depending on the length of treatment (Alleva et al, 1996;Parikh et al, 2004a, b, c;; reviewed by Terry and Mahadik, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 represents the predominant caspase in the CNS, both in normal neurodevelopment and in neuropathological [23,24]. In the present study, chronic administration of Al could activate caspase-3 in rat brain (Fig.…”
Section: Apoptotic Studiessupporting
confidence: 58%
“…Caspase-3 represents the predominant caspase in the CNS, both in normal neurodevelopmental and in neuropathological states (Jarskog et al 2007;Yuan and Yankner 2000). In the previous studies using western blotting, 40-55% increase in immunoreactivity of activated caspase-3 bands after the chronic administration of haloperidol was observed.…”
Section: Discussionmentioning
confidence: 94%